The Effect of Management Changes, Audit Fees, and Return on Assets Percentage Changes on Auditor Switching: A Study of Banking Companies Listed on the Indonesia Stock Exchange (2018–2024) - Rifka Khairunnisa; Abdul Pattawe; Tenripada (www.amertainstitute.com, 2025)
This study aims to analyze the effect of management changes, audit fees, and percentage changes in return on assets on auditor switching in banking companies listed on the Indonesia Stock Exchange from 2018 to 2024. Through a quantitative approach and purposive sampling method, the sample used in this study amounted to 70. The results of this study were tested with descriptive analysis statistical tests, logistic regression, overall model fit, Hosmer and Lemeshow Goodness of Fit, and the coefficient of determination. With the results showing that management changes, audit fees, and percentage changes in return on assets have no voluntary effect on auditor switching. This study also indicates that some of the company's internal factors are not enough to be the reason for the company to do auditor switching, especially companies engaged in the banking sector.